NEW TECHNOLOGIES TO SUPPORT LANGUAGE LEARNING ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2026)
The rapid development of digital technologies has reshaped language learning by offering new possibilities for personalization, interaction, and accessibility. This article examines key emerging tools-including artificial intelligence, mobile applications, virtual and augmented reality, and adaptive platforms-and their role in enhancing vocabulary, pronunciation, grammar, and communication skills. The study also discusses pedagogical benefits such as increased learner autonomy and flexible learning environments, alongside challenges related to digital literacy and technological resources. Overall, the findings show that when applied effectively, new technologies can significantly improve the efficiency and innovation of language learning.